Enhanced Lacto-Tri-Peptide Bio-Availability by Co-Ingestion of Macronutrients - Ten Have, Gabriella A. M.; van der Pijl, Pieter C.; Kies, Arie K.; Deutz, Nicolaas E. P. (PLOS ONE, 2015)
Some food-derived peptides possess bioactive properties, and may affect health positively. For example, the C-terminal lacto-tri-peptides Ile-Pro-Pro (IPP), Leu-Pro-Pro (LPP) and Val-Pro-Pro (VPP) (together named here XPP) are described to lower blood pressure. The bioactivity depends on their availability at the site of action. Quantitative trans-organ availability/kinetic measurements will provide more insight in C-terminal tri-peptides behavior in the body. We hypothesize that the composition of the meal will modify their systemic availability. We studied trans-organ XPP fluxes in catheterized pigs (25 kg; n=10) to determine systemic and portal availability, as well as renal and hepatic uptake of a water-based single dose of synthetic XPP and a XPP containing protein matrix (casein hydrolyte, CasH). In a second experiment (n=10), we compared the CasH-containing protein matrix with a CasH-containing meal matrix and the modifying effects of macronutrients in a meal on the availability (high carbohydrates, low quality protein, high fat, and fiber). Portal availability of synthetic XPP was 0.08 ± 0.01% of intake and increased when a protein matrix was present (respectively 3.1, 1.8 and 83 times for IPP, LPP and VPP). Difference between individual XPP was probably due to release from longer peptides. CasH prolonged portal bioavailability with 18 min (absorption half-life, synthetic XPP: 15 ± 2 min, CasH: 33 ± 3 min, p<0.0001) and increased systemic elimination with 20 min (synthetic XPP: 12 ± 2 min; CasH: 32 ± 3 min, p<0.0001). Subsequent renal and hepatic uptake is about 75% of the portal release. A meal containing CasH, increased portal 1.8 and systemic bioavailability 1.2 times. Low protein quality and fiber increased XPP systemic bioavailability further (respectively 1.5 and 1.4 times). We conclude that the amount and quality of the protein, and the presence of fiber in a meal, are the main factors that increase the systemic bioavailability of food-derived XPP.